Children, adults, and shared responsibilities Jewish, Christian, and Muslim perspectives - Bunge, Marcia J. (Marcia JoAnn), 1954- (Cambridge, [England] : Cambridge University Press, 2012)
"This collection of essays by Jewish, Christian and Muslim scholars underscores the significance of sustained and serious ethical, interreligious and interdisciplinary reflection on children. Essays in the first half of the volume discuss fundamental beliefs and practices within the religious traditions of Judaism, Christianity and Islam regarding children, adult obligations to them, and a child's own obligations to others. The second half of the volume focuses on selected contemporary challenges regarding children and faithful responses to them. Marcia J. Bunge brings together scholars from various disciplines and diverse strands within these three religious traditions, representing several views on essential questions about the nature and status of children and adult-child relationships and responsibilities. The volume not only contributes to intellectual inquiry regarding children in the specific areas of ethics, religious studies, children's rights and childhood studies, but also provides resources for child advocates, religious leaders and those engaged in interreligious dialogue"--
"This collection of essays by Jewish, Christian, and Muslim scholars underscores the significance of sustained and serious ethical, interreligious, and interdisciplinary reflection on children. Essays in the first half of the volume discuss fundamental beliefs and practices within the religious traditions of Judaism, Christianity, and Islam regarding children, adult obligations to them, and a child's own obligations to others. The second half of the volume focuses on selected contemporary challenges regarding children and faithful responses to them. Marcia J. Bunge brings together scholars from various disciplines and diverse strands within these three religious traditions, representing several views on essential questions about the nature and status of children and adult-child relationships and responsibilities. The volume not only contributes to intellectual inquiry regarding children in the specific areas of ethics, religious studies, children's rights, and childhood studies, but also provides resources for child advocates, religious leaders, educators, and those engaged in interreligious dialogue"--
Machine generated contents note: Introduction Marcia J. Bunge; Part I. Religious Understandings of Children and Obligations to Them: Central Beliefs and Practices: 1. The concept of the child embedded in Jewish law Elliot N. Dorff; 2. Children's spirituality in the Jewish narrative tradition Sandy Eisenberg Sasso; 3. Christian understandings of children and obligations to them: central Biblical themes and resources Marcia J. Bunge; 4. Human dignity and social responsibility: Catholic Social Thought on children William Werpehowski; 5. Islam, children, and modernity -- a Qur'anic perspective Farid Esack; 6. Linking past and present: educating Muslim children in diverse cultural contexts Lily Zakiyah Munir and Azim Nanji; 7. Imagining childism: how childhood should transform religious ethics John Wall; 8. Talking about childhood and engaging children: a Christian perspective on interfaith dialogue Nelly Van Doorn-Harder; Part II. Specific Responsibilities of Children and Adults: Selected Contemporary Issues and Challenges: 9. Will I have Jewish grandchildren?: Cultural transmission and ethical concerns among ethnoreligious minorities Sylvia Barack Fishman; 10. Muslim youth and religious identity: classical perspectives and contemporary challenges Marcia Hermansen; 11. Honor your father and your mother: a Christian perspective in dialogue with contemporary psychological theories Annemie Dillen; 12. Work, play, labor, and chores: Christian ethical reflection on children and vocation Bonnie Miller-McLemore; 13. Orphans and adoption: Biblical themes, Christian initiatives, and contemporary ethical concerns Keith Graber Miller; 14. Second-hand children: a Jewish ethics of foster care in an age of desire Laurie Zoloth; 15. Christianity's mixed contributions to children's rights: traditional teachings, modern doubts Don Browning and John Witte, Jr; 16. Children's rights in modern Islamic and international law: changes in Muslim moral imaginaries Ebrahim Moosa; Appendix I. Selected primary texts; Appendix II. United Nations Convention on the Rights of the Child; Index of names; Index of subjects.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Children -- Conduct of life; Children -- Religious aspects; Children -- Religious life; Children and adults; Conduct of life; Children's rights -- Religious aspects; RELIGION / Ethics; RELIGION / Christianity / General; Electronic books